Imre Lakatos on Identifying the Problems of Demarcation and the Growth of Science - Grigoryan, Kristine (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
Imre Lakatos, identifying the problems of demarcation and the growth of science, argues that it is necessary to assess not the separate theories but the changes taking place in the scientific mosaic. The steps which contribute to the increase of the empirical content, are considered to be progressive, i.e. scientific, while the steps that reduce the empirical content are considered to be regressive, i.e. non-scientific.
Keywords: the philosophy of science, the problem of demarcation, the problem of the growth of science, the problem of induction, the empirical content, Ad hoc, Imre Lakatos